A graphene oxide-wrapped bipyramidal sulfur@polyaniline core–shell structure as a cathode for Li–S batteries with enhanced electrochemical performance. Issue 17 (11th April 2016) - Zhang, Kailong; Xu, Yanhua; Lu, Yue; Zhu, Yongchun; Qian, Yuying; Wang, Danfeng; Zhou, Jianbin; Lin, Ning; Qian, Yitai
Abstract : Composites of the graphene oxide-wrapped bipyramidal sulfur@polyaniline core–shell structure have been prepared and investigated as cathodes for Li–S batteries. Abstract : Composites of the graphene oxide-wrapped bipyramidal sulfur@polyaniline core–shell structure (S@PANI/GO) have been prepared at low temperature. The FT-IR and Raman spectra illustrated the chemical effect between PANI and GO, and the SEM images illustrated the tight connection with each other. As a cathode for Li–S batteries, the S@PANI/GO composite demonstrated better electrochemical performance than S@PANI, or S/GO composites. The S@PANI/GO composite delivered enhanced cycle stability (0.2 C, 875 mA h g −1 after 100 cycles) and high-rate capability (4 C, 466 mA h g −1 ). Even at 1 C, the S@PANI/GO composite still delivered a capacity of 641 mA h g −1 after 300 cycles. The enhanced performance should benefit from the core–shell structure with a synergistic effect between polyaniline and graphene oxide.